Metachromatic Leukodystrophy Presenting with Multiple Cranial Nerve and Lumbosacral Nerve Root Enhancement Without White Matter Changes - Ruben Jauregui; Mekka R. Garcia; Thomas Mehuron; Steven L. Galetta; Devorah Segal (Neurology International, 2025)
Background: Metachromatic leukodystrophy (MLD) is a rare autosomal recessive disorder that causes demyelination of both the central (CNS) and peripheral nervous systems (PNS). Objective: This study aims to report a unique MLD case presenting with cranial neuropathies and ataxia, initially without white matter changes on MRI, leading to diagnostic uncertainty. Results: A 20-month-old presented with bilateral abduction deficits, facial diplegia, and ataxia, raising the possibility of an acquired demyelinating condition. An MRI scan showed the enhancement of multiple cranial nerves, but normal white matter. A follow-up MRI showed new white matter changes that spared the U-fibers, suggesting a leukodystrophy. Biochemical assays were suggestive of metachromatic leukodystrophy, which was confirmed with genetic testing demonstrating a homozygous c.848+3A > G variant in ARSA. Conclusions: Our patient suggests that the initial presentation of MLD may mimic an acquired demyelinating condition and manifest with multiple cranial nerve palsies before more typical white matter changes evolve.